The adaptor protein SAP regulates type II NKT‐cell development, cytokine production, and cytotoxicity against lymphoma. Issue 12 (28th October 2014) - Weng, Xiufang; Liao, Chia‐Min; Bagchi, Sreya; Cardell, Susanna L.; Stein, Paul L.; Wang, Chyung‐Ru
Abstract : CD1d‐restricted NKT cells represent a unique lineage of immunoregulatory T cells that are divided into two groups, type I and type II, based on their TCR usage. Because there are no specific tools to identify type II NKT cells, little is known about their developmental requirements and functional regulation. In our previous study, we showed that signaling lymphocytic activation molecule associated protein (SAP) is essential for the development of type II NKT cells. Here, using a type II NKT‐cell TCR transgenic mouse model, we demonstrated that CD1d‐expressing hematopoietic cells, but not thymic epithelial cells, meditate efficient selection of type II NKT cells. Furthermore, we showed that SAP regulates type II NKT‐cell development by controlling early growth response 2 protein and promyelocytic leukemia zinc finger expression. SAP‐deficient 24αβ transgenic T cells (24αβ T cells) exhibited an immature phenotype with reduced Th2 cytokine‐producing capacity and diminished cytotoxicity to CD1d‐expressing lymphoma cells. The impaired IL‐4 production by SAP‐deficient 24αβ T cells was associated with reduced IFN regulatory factor 4 and GATA‐3 induction following TCR stimulation. Collectively, these data suggest that SAP is critical for regulating type II NKT cell responses. Aberrant responses of these T cells may contribute to the immune dysregulation observed in X‐linked lymphoproliferative disease caused by mutations in SAP.